Educator Character Formation Through Islamic Ethical Values: Insight From KH. Hasyim Asy’ari’s Adab al-‘Alim wa al-Muta’allim - Jumadil Awali Habibullah; Nur Hidayat; Hery Noer Aly (Journal of Social and Humanities, 2026)
Character education has become a critical issue in contemporary education due to increasing moral challenges, rapid social change, and the declining role of educators as ethical role models. Although previous studies have examined KH. Hasyim Asy'ari's educational thought, few have systematically classified his ethical principles into a comprehensive framework for educator character formation. This study aims to analyze and classify the ethical values of educators articulated in Adab al-'Alim wa al-Muta'allim. Using a qualitative library research approach with content analysis, the study examines the ethical principles embedded in the text through coding, categorization, and thematic interpretation. The findings reveal three major domains of educator ethics: educators' ethics toward themselves, toward the teaching profession, and toward students. Across these domains, 42 ethical values were identified and synthesized into 19 core values, which were further organized into four interconnected character dimensions: spiritual, moral, professional, and social. The novelty of this study lies in its systematic classification of KH. Hasyim Asy'ari's ethical thought into a structured framework for educator character formation, rather than merely describing his educational philosophy. The study contributes conceptually to Islamic educational ethics by providing an integrated framework that can support contemporary educator character development and strengthen the ethical foundations of professional teaching practice.